Autonomy and dependence – experiences of home abortion, contraception and prevention. Issue 3 (22nd August 2012) - Makenzius, Marlene; Tydén, Tanja; Darj, Elisabeth; Larsson, Margareta
<x xml:space="preserve">Abstract</x> Background: Few studies have explored experiences and needs in relation to an induced medical abortion with the final treatment at home. Objective: To explore women's and men's experiences and needs related to care in the context of a home abortion as well as to elicit their views on contraception and prevention of unwanted pregnancies. Method: Qualitative interviews were carried out with 24 women and 13 men who had experienced a home abortion; they took place in Sweden during 2009/10. Results: Two overarching themes were identified: Autonomy– the decision to undergo an abortion and the choice of method were well considered by the woman, supported by the partner. The home environment increased their privacy and control, which helped them freely express and share their emotions. They were motivated to avoid a subsequent abortion and considered it an individual responsibility; however, contraceptive follow‐up visits were rare. Dependence– a desire to be treated with empathy and respect by care providers and to receive adequate information. In the prevention of unwanted pregnancies, financial resources, improved communication/education and subsidized contraceptives were considered important. Conclusion: Home abortion increases autonomy, and women and partners demonstrate self‐care ability. This autonomy, however, is related to dependence: a desire to be treated with empathy and respect on equal terms and to receive adequate information tailored to their self‐care needs. Routines in abortion care should be continuously evaluated to ensure care satisfaction, safety and security as well as contraceptive adherence.